Near-Neighbor Interactions in the NS3-4A Protease of HCV Impact Replicative Fitness of Drug-Resistant Viral Variants. Issue 12 (31st May 2019) - Doncheva, Nadezhda T.; Domingues, Francisco S.; McGivern, David R.; Shimakami, Tetsuro; Zeuzem, Stefan; Lengauer, Thomas; Lange, Christian M.; Albrecht, Mario; Welsch, Christoph
Abstract: A variety of amino acid substitutions in the NS3-4A protease of the hepatitis C virus lead to protease inhibitor (PI) resistance. Many of these significantly impair the replication fitness of the resistant variants in a genotype- and subtype-dependent manner, a critical factor in determining the probability with which resistant variants will persist. However, the underlying molecular mechanisms are unknown. Here, we present a novel residue-interaction network approach to determine how near-neighbor interactions of PI resistance mutations in NS3-4A can impact protease functional sites dependent on their genomic background. We constructed subtype-specific consensus residue networks for subtypes 1a and 1b from protease structure ensembles combined with biological properties of protein residues and evolutionary amino acid conservation. By applying local and global network topology analysis and visual exploration, we characterize PI resistance-associated sites and outline differences in near-neighbor interactions. We find local residue-interaction patterns and features at protease functional sites that are subtype specific. The noncovalent bonding patterns indicate higher fitness costs conferred by PI resistance mutations in a subtype 1b genomic background and explain the prevalence of Q80K and R155K in subtype 1a. Based on local residue interactions, we predict a subtype-specific role for the protease residue NS3–Q80 in molecular mechanisms related to the assembly of infectious virus particles that is supported by experimental data on the capacity of Q80K variants to replicate and produce infectious virus in subtype 1a and 1b cell culture. Graphical abstract: Unlabelled Image Highlights: A novel graph-based approach is applied to characterize multiple NS3-4A structure models. Residue-interaction patterns at PI resistance sites are HCV subtype specific. PI resistance sites are closer to NS3-4A protease functional sites in subtype 1b than 1a. NS3–Q80K impairs infectious virus particle assembly specifically in subtype 1b. This paper highlights subtype-specific molecular mechanisms in RAV persistence.